Research on adaptive dimming management methods for intelligent lighting systems in port traffic based on ocean weather perception - Jiang, Haoyu; Zhao, Xiaolong; Zhang, Zeguo; Ji, Jiacheng (Frontiers in Marine Science, 2024)
In challenging visibility conditions, the reliability of existing port lighting systems is significantly affected by abrupt changes in environmental factors (primarily stemming from ocean weather).This study proposes a cloud-edge collaborative dimming model that integrates a combined filter, enabling dynamic adaptation to these weather variations to ensure the stability of the lighting system. Additionally, the application of edge computing not only alleviates computational pressure but also facilitates the model's ability to achieve effective regional adaptive dimming in accordance with environmental regulations. Experimental results indicate that this method is suitable for scenarios with unknown mutations under extreme conditions, providing a more reliable and intelligent solution for port lighting systems within the Internet of Things (IoT) framework.